Avaliação do desempenho zootécnico do camarão marinho litopenaeus vannamei cultivado com bactérias autóctones - Costa, Vinícius Barbosa da (Universidade Federal Rural do Semi-Árido, 2021)
The term probiotic, in aquaculture, applies to the use of live microbial supplements that have a beneficial effect on the host and the growing environment. However, the bacteria with higher yield as probiotics, should be isolated from the organisms of origin, that is, from the animal or environment itself, and have gram positive characteristics, because that way there would be better adaptation of the bacteria, as they would be more used to the bacteria. their intrinsic conditions. In this sense, the present study aimed to verify the efficacy of a probiotic made from a group of bacteria isolated from the intestinal tract of cultivated shrimp, evaluating its zootechnical viability compared to a commercial probiotic in the cultivation of marine shrimp Litopenaeus vannamei. The zootechnical parameters showed significant differences (p> 0.05) between treatments. The treatments developed in salinity 35 ppt showed better survival results for all treatments, with the highest survival recorded for the treatments where there was the application of the autochthonous probiotic, PAA and PA, respectively. Comparatively, these treatments did not show good results in crops with low salinity. The physical-chemical parameters of the water, such as temperature, pH and dissolved oxygen, remained stable between treatments and are within the optimal growth range of L. vannamei shrimp, with no significant differences (p <0.05). The use of autochthonous bacteria as probiotics in shrimp cultivation was efficient for both treatments (PA and PAA), since in low salinities the use of this compound must be continuous, in order to avoid disturbances in the levels of nitrogen compounds.
Keywords: Camarão cultivado; Biotecnologia; Bactérias benéficas; Bactérias autóctones; Cultivated shrimp; Biotechnology; Beneficial bactéria; Autochthonous bactér; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA